KARAKTERISTIK PENDERITA PENYAKIT DEMAM BERDARAH DENGUE (DBD) YANG DIRAWAT INAP DI RSUP HAJI ADAM MALIK MEDAN TAHUN 2015-2016 - Sara Vela Purba; Sori Muda Sarumpaet; Fazidah A Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
ABSTRACT DHF until now is a public health problem in Indonesia that the number of patients and the area of ​​its spread is increasing. Based on Ministry of Health of Indonesia (2016) obtained the incidence rate of dengue patients equal to 50,75 per 100.000 population and Case Fatality Rate (CFR) 0.83%. The purpose of this study was to determine the characteristics of DHF patients treated in Haji Adam Malik Central Public Hospital Medan in 2015-2016. This is a descriptive study with case series design. Population is all data of patient DHF which are 136 and as a sample in this study (total sampling). Data was analyzed by Chi-Square, Exact-Fisher and Kolmogorov-Smirnov. The results shows that the highest proportion of respondens was by age 15-44 years (50,0%), males (56,6%), Protestant (53,7%), students/college (43,4), lives in Medan (56,6%). The platelet count >100,000/μl (53,7%), percentage of hematocrit ≥20% (85,3%), first degree (87,5%), cured (91,9%), average treatment duration 5,00 days, medical treatment of infusion and drug (98,9%), cost by ASKES/BPJS/KIS (Health insurance) (80,9%), negative IgG (33,1%), negative IgM (44,1%). There was a difference between the emergency by severity (p=0,048). There was no significant difference between the hematocrit numbers by the severity (p=0,076), by age (p=0,334), circumstances such as return by age (p=0,999) based on examination of IgG (p=0,452), severity by IgM examination (p=1,000). It was recommended that hospital completed data in medical record, laboratory examination results. Keywords: DHF, patient characteristic, Adam Malik Hospital